2015
DOI: 10.1007/s12094-015-1410-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the PI3K signaling pathway: buparlisib as a new targeted option in breast carcinoma

Abstract: Aberrations in the PI3K signaling pathway are frequently observed in patients with breast cancer. Because of that, PI3K inhibitors are attractive options for the treatment of breast cancer because PI3K is the most proximal component of the pathway other than receptor tyrosine kinases. Buparlisib is a potent and highly specific oral pan-class I PI3K inhibitor, which is currently under investigation in patients with breast cancer. In this article, we describe the PI3K signaling pathway, the prognostic value of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Genomic alterations in PIK3CA , the gene encoding the catalytic subunit of PI3K, are common in ER+ tumors [28 ● ,29,30]. It is thought that suppression of the PI3K/AKT/mTOR pathway can lead to increased activity of ER, facilitating resistance, and therefore many groups have used preclinical models to elucidate the mechanisms of PI3K/AKT/mTOR pathway inhibitors and the influence these compounds have on estrogen-mediated signaling [19 ● ,21 ●● ,25,3133]. …”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Genomic alterations in PIK3CA , the gene encoding the catalytic subunit of PI3K, are common in ER+ tumors [28 ● ,29,30]. It is thought that suppression of the PI3K/AKT/mTOR pathway can lead to increased activity of ER, facilitating resistance, and therefore many groups have used preclinical models to elucidate the mechanisms of PI3K/AKT/mTOR pathway inhibitors and the influence these compounds have on estrogen-mediated signaling [19 ● ,21 ●● ,25,3133]. …”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…The third pathway analyzed in our study was the PI3K pathway, which was found altered in 139 (56.3%) cases. It is reported that alteration of the PI3K pathway is mainly observed in HR‐positive diseases . The highest alteration rate of the PI3K pathway was found in HR+HER2− breast cancers (Table ).…”
Section: Discussionmentioning
confidence: 95%
“…It is reported that alteration of the PI3K pathway is mainly observed in HR-positive diseases. 47 The highest alteration rate of the PI3K pathway was found in HR+HER2− breast cancers (Table S2). In addition, aberrant activation of the PI3K pathway is related to resistance to endocrine therapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K phosphorylates phosphatidylinositol 4,5 biphosphate (PIP2) to phosphatidylinositol 3,4,5 triphosphate (PIP3) and later the accumulation of PIP3 at the membrane leads to the recruitment of AKT and its following phosphorylation by PDK1 and mTORC2. [6,7,8] Some of the paths by which activated AKT promotes cell growth, and survival are:…”
Section: Treatment In Endocrine Therapy-resistant Casesmentioning
confidence: 99%
“…Buparlisib is also the subject of a phase II trial of paclitaxel combined with trastuzumab in HER2-overexpressing BC (NCT01816594). [5,8,24] The use of isoform-specific PIs is just one of the approaches to attain notable pathway suppression clinically with favorable adverse effect outline. Every isoform has a is involved in a specific way in normal physiological processes and disease.…”
Section: Pi3k Inhibitorsmentioning
confidence: 99%